The effectiveness of service quality towards customer satisfaction provided by insurance company at Bangsar, Kuala Lumpur / Nabilahuda Mohd Alamin - Mohd Alamin, Nabilahuda (Faculty of Business and Management, 2014)
This research study is about the effectiveness of service quality towards customer satisfaction provided by Insurance Company at Bangsar, Kuala Lumpur. Dimension of service quality and customer satisfaction have been identified in order to investigate the relationship between dimensions of service quality towards customer satisfaction at Bangsar, Kuala Lumpur. The survey was conducted at Menara Telekom and Bangsar Village. The sample for this study is 120 respondents. Data obtained by using primary data. Respondent are required to answer the questionnaire that contain of element that potentially have relationship with the service quality and customer satisfaction. Data analyzed by using reliability test, frequency test, Descriptive Statistics, Pearson correlation analysis, and regression analysis through SPSS program. The result shows that the entire three dimensions in service quality have significant relationship towards customer satisfaction. Moreover, the result also shows that rank contribution towards customer satisfaction is responsiveness followed by reliability and assurance. Conclusion and recommendation are made.